2005
DOI: 10.1074/jbc.m504766200
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 and Histone 3 Trimethyl Lysine 27 Associated with Il4 and Il13 Gene Silencing in TH1 Cells

Abstract: Differentiation of naïve CD4 T cells toward the T helper 1 (T H 1) and T helper 2 (T H 2) fates involves the transcriptional repression and enhancement, respectively, of Il4 and Il13, adjacent chromosome 11 genes encoding the canonical T H 2 cytokines interleukin-4 and interleukin-13. Proper execution of this developmental fate choice during immune responses is critical to host defense and, when misregulated, leads to susceptibility to infectious microbes and to allergic and autoimmune diseases. Here, using ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 25 publications
3
108
1
3
Order By: Relevance
“…T-bet directly activates IFNG and represses IL4 (Fig. 5E) (23,27) whereas GATA3 acts in the opposite manner to activate IL4 and represses IFNG (22,28). Although both factors are coexpressed in human Th1 cells, T-bet activity would appear to be dominant and these cells exhibit an expression pattern that can be recapitulated in murine T-cells by expression of T-bet in the absence of IFN␥.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-bet directly activates IFNG and represses IL4 (Fig. 5E) (23,27) whereas GATA3 acts in the opposite manner to activate IL4 and represses IFNG (22,28). Although both factors are coexpressed in human Th1 cells, T-bet activity would appear to be dominant and these cells exhibit an expression pattern that can be recapitulated in murine T-cells by expression of T-bet in the absence of IFN␥.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Th2 differentiation is accompanied by hyperacetylation of the IL4/IL5/ IL13 locus, dependent on GATA-3 (18,19,(23)(24)(25)(26). Recent murine studies also show that T-bet directly represses the expression of IL4 (23,27) and that GATA3 directly represses IFNG (22,28). This suggests that T-bet and GATA-3 may act to promote alternative pathways of T-cell differentiation by acting on the same target genes.…”
mentioning
confidence: 92%
“…Indeed, histone acetylation of promoters has been correlated with transcriptional activation, although this correlation is not exclusive, and generally precedes transcription of many genes. For example, histone H3 can undergo a variety of post-transcriptional modifications: acetylation of K9 and K14 residues (H3-K9/K14 ac ), methylation of K4 and phosphorylation of S10 are associated with transcription, and dimethylation of K9 and tri-methylation of K9 or K27 are associated with silencing [52,53]. Chromatin immunoprecipitation assays (ChIP) using anti-H3-K9/ K14 ac on nuclei prepared from BM3.3 CD8 T cells stimulated by the full or partial agonist revealed that strong BM3.3 TCR engagement induces rapid acetylation of H3 (at 24 h) on promoter regions of genes characteristic of effector CD8 T cell differentiation, such as cd25, gzmB and Lta.…”
Section: Molecular Events Required For Overcoming Activation Thresholmentioning
confidence: 99%
“…Biochemical studies have identified the existence of protein complexes that contain both H3K27-demethylase and H3K4-methyltransferase activities, which has led to speculation that at least in some circumstances, there may be a simultaneous reorganization of both repressive and permissive chromatin states at target promoters (Agger et al 2008). In fact, when examining the status of methylation modifications on nucleosomes, a mutually exclusive series of nonpermissive-such as H3K9me3 and H3K27me3-versus permissive-such as H3K4me2 and H3K4me3-marks has been observed in locus-specific studies of differentiated cell types (Koyanagi et al 2005;Mikkelsen et al 2007;Schoenborn et al 2007). However, these histone methylation patterns are not strictly created in an "all or none" fashion, as bivalent chromatin domains that contain both repressive and permissive modifications are found in pluripotent cells (Mikkelsen et al 2007).…”
mentioning
confidence: 99%